2012
DOI: 10.1345/aph.1r362
|View full text |Cite
|
Sign up to set email alerts
|

Bioidentical Progesterone Cream for Menopause-Related Vasomotor Symptoms: Is it Effective?

Abstract: Available evidence from RCTs does not support the efficacy of bioidentical progesterone cream for the management of menopause-related vasomotor symptoms. Adverse effects appear to be mild and self-limiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…Custom compounded bioidentical hormones are not recommended because data supporting claims that they are safer and more effective than standard hormones are lacking. 117,118 Young cancer survivors experiencing menopause at an early age can consider oral contraceptives or MHT for symptom relief and potential cardiac and bone benefits as long as not contraindicated.…”
Section: Menopausementioning
confidence: 99%
See 1 more Smart Citation
“…Custom compounded bioidentical hormones are not recommended because data supporting claims that they are safer and more effective than standard hormones are lacking. 117,118 Young cancer survivors experiencing menopause at an early age can consider oral contraceptives or MHT for symptom relief and potential cardiac and bone benefits as long as not contraindicated.…”
Section: Menopausementioning
confidence: 99%
“…In one study of breast cancer survivors, the control group used a nonhormonal moisturizer and saw a transient improvement in vaginal symptoms. 118 Topical anesthetics may help with vaginal pain as demonstrated in a study of 46 breast cancer survivors that found that application of lidocaine to the vulvar vestibule before vaginal penetration improved dyspareunia. 208 …”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…Krem formuyla yapılmış 4 randomize kontrollü çalışmada, transdermal biyo-özdeş progesteron vazomotor semptomların tedavisinde plasebodan daha etkili bulunmamıştır. [16][17][18][19][20] Genel olarak iyi tolere edilmelerine karşın, baş ağrısı ve kısa süreli vajinal kanamalar yakınma nedeni oluşturmuştur. 20 AMERİKAN KADIN HASTALIKLARI VE DOĞUM (ACOG) VE ÜREME TIBBI (ASRM) UZMAN DERNEK GÖRÜŞLERİ 21,22 1.…”
Section: İstenmeyen Etki̇ler Görülebi̇li̇r Mi̇?unclassified
“…[16][17][18][19][20] Genel olarak iyi tolere edilmelerine karşın, baş ağrısı ve kısa süreli vajinal kanamalar yakınma nedeni oluşturmuştur. 20 AMERİKAN KADIN HASTALIKLARI VE DOĞUM (ACOG) VE ÜREME TIBBI (ASRM) UZMAN DERNEK GÖRÜŞLERİ 21,22 1. Biyo-özdeş ısmarlama alaşım bileşimlerinin geleneksel, ticari menopoz hormon tedavilerine üs-tünlüklerini gösteren bir kanıt yoktur.…”
Section: İstenmeyen Etki̇ler Görülebi̇li̇r Mi̇?unclassified
“…4,18 A recent review of RCTs also concluded that bioidentical progesterone cream is not effective for the relief of vasomotor symptoms associated with menopause. 19 FDA-approved progestogens (including the bioidentical variety of oral micronized progesterone) are the only preparations that have been proven to reliably protect women from endometrial hyperplasia and cancer and should be included in the HT regimen for any woman with a uterus. Compounded preparations of BHT that are not FDA-approved may provide women with a false sense of protection from endometrial cancer.…”
Section: Casementioning
confidence: 99%